The horse who sings : Radical art from Croatia. - Cramer, Sue; Museum of Contemporary Art, Zagreb (Sydney : Museum of Contemporary Art, 1993)
Gorgona ; Knifer, Julije ; Mangelos, Dimitrije Basicevic ; Dimitrijevic, Braco ; Trbuljak, Goran ; Stilinovic, Mladen ; Demur, Group of Six Authors (Boris ; Jerman, Zeljko ; Martek, Vlado ; Stilinovic, Mladen ; Vucemilovic), Fedor ; Martek, Vlado ; Delimar, Vlasta
12 p. : zw/w ill. ; 42 x 29,5 cm : groot formaat
biografie
The horse who sings : Radical art from Croatia, Museum of Contemporary Art, Sydney, 17 March - 27 May 1993
Engels
kunstcatalogus